The Influence of ROA, DER, and Tax Planning on Corporate Income Tax Payable (A Study on Mining Companies Listed on the Indonesia Stock Exchange for the Period 2017 - 2021) - Agustiyani Agustiyani; Minanari Minanari (Universitas Mercu Buana, 2024)
This study aims to analyze the influence of company value, leverage, profitability, and institutional ownership on tax avoidance (an empirical study on the telecommunication company sector listed on the Indonesia Stock Exchange for the period 2020-2023). The type of research used is quantitative research. The population in this study is the telecommunication company sector listed on the Indonesia Stock Exchange for the period 2020-2023. The sampling method in this study uses a purposive sampling technique. Purposive sampling is a method used in sample selection where 11 companies were selected over 4 years with a total sample of 44. The data collection technique used in this study is a documentation technique by obtaining data in the form of company annual reports for 2020–2023 and a literature study technique by conducting a literature review and reviewing various sources, such as books, journals, and other sources related to the research. The analysis method used is a multiple linear regression model with the help of the SPSS version 25 program. The results of the study indicate that the company value variable has a positive effect on tax avoidance, leverage has no effect on tax avoidance, profitability has no effect on tax avoidance, and institutional ownership has a positive effect on tax avoidance.